Influences of Stir and Viscosity Coefficient on the Formation of Hotspots During Microwave Heating - GUO, QING-GONG; YANG, XIAO-QING; YANG, LI-JUN (Asian Journal of Chemistry, 2010)
A numerical model was presented to study the microwave heating on saline water, in order to study on the influences of stir and viscosity coefficient on the formation of hotspots during microwave heating on saline water. The coupled Maxwell's equations, fluid field equations and heat transport equations were solved by using finite-element (FEM) method. The results show that hotspots can't be completely dispelled by stir. In case of the certain stir, the lower the viscosity coefficient, the easier the hotspots occur while the vice versa without stir.